Real-world risk exposure in older drivers with cognitive and visual dysfunction. (25th November 2019) - Merickel, Jennifer; High, Robin; Dawson, Jeffrey; Rizzo, Matthew
Abstract: Objective: This study addresses the need to measure and monitor objective, real-world driver safety behavior in at-risk drivers with age-related dysfunction. Older drivers are at risk for age-related cognitive and visual dysfunction, which may reduce mobility and increase errors that lead to crashes. Understanding patterns of real-world behavior, exposure, and cognitive–perceptual processes underlying risk in environmental context and in older drivers requires new approaches. Methods: We assessed patterns of objective, real-world driver risk exposure and vehicle control related to steering, braking, and accelerating in older adults with a range of cognitive and visual functional abilities. Real-world driver behavior was collected from passive-monitoring systems installed in 77 drivers' vehicles and analyzed across 242, 153 km (150, 467 miles) driven. Driver behavior was assessed cross-sectionally in relationship to driver functional abilities and safety-critical environmental contexts (roadway type and visibility condition). Results: Results suggest that cognitive dysfunction impairs vehicle control across wide-ranging environments. Drivers with greater cognitive dysfunction showed more erratic braking and accelerating during daytime commercial and interstate driving. Drivers with less cognitive dysfunction showed more erratic braking and accelerating on residential roadways regardless of visibility condition. Greater cognitive dysfunction predicted more erratic steering on commercial and interstate roadways and less erratic steering on residential roadways. Greater visual dysfunction impaired braking and accelerating during nighttime and interstate driving, but not on residential or commercial roadways. Steering behavior was unaffected by visual abilities. Drivers with greater cognitive dysfunction did not appear to reduce driving frequency in higher-risk environments. Visually impaired drivers drove more on residential roadways and less on commercial roadways, but did not reduce driving on interstates, where they showed the greatest risk per mile driven. Conclusions: Results successfully mapped driver cognitive and visual profiles onto contemporaneous, real-world behavior and risk loci. Results link age-related dysfunction to real-world vehicle control and show that drivers may not sufficiently reduce exposure to higher-risk driving environments. Employing naturalistic observation to monitor and measure patterns of driver behavior can inform methods for early detection of age-related risk, fitness-to-drive assessments, and interventions to preserve safety, mobility, and quality of life in aging or other at-risk populations.